Resposta funcional comparada entre Harmonia axyridis (Pallas), Cycloneda sanguinea (Linnaeus) e Hippodamia convergens Guerin Meneville (Coleoptera: Coccinellidae) alimentadas com Brevicoryne brassicae (Linnaeus) (Hemiptera: Aphididae) - Milléo, Julianne; Moral, Rafael de Andrade; Fernandes, Francisco Sales; Godoy, Wesley Augusto Conde (EntomoBrasilis, 2019)
Resumo. O presente estudo teve como objetivos avaliar a resposta funcional dos instares larvais e adultos de três espécies de coccinelídeos predadores [Harmonia axyridis (Pallas), Cycloneda sanguinea (Linnaeus) e Hippodamia convergens Guerin Meneville] em diferentes densidades de Brevicoryne brassicae (Linnaeus), comparando o desempenho da espécie invasora com as espécies locais. Observou-se que H. axyridis consumiu mais insetos que as outras espécies; o número de pulgões predados pelas três espécies de coccinelídeos aumentou com a troca do instares larvais e, que as fêmeas tenderam a predar mais pulgões que os machos. A voracidade das larvas de 4º instar é similar a dos adultos, às vezes até maior, como no caso da C. sanguinea. Exceto no 1º instar larval, todos os outros estágios de vida mostraram aumento do consumo de pulgões à medida que a oferta de presas aumenta. Os resultados mostraram que a resposta funcional do tipo III foi indicada apenas pelas larvas de 3º instar de H. axyridis e nas demais espécies e estágios avaliados a resposta funcional foi do tipo II. Em geral H. axyridis apresentou assíntotas das respostas funcionais mais elevadas em comparação com as espécies anteriormente estabelecidas. Entretanto, a diferença entre a magnitude das curvas de respostas funcionais entre a invasora e as espécies locais não é muito acentuada, o que pode indicar pouco impacto da invasora sobre a população de recursos no campo e, uma tendência a adaptação e estabilização entre estas espécies da comunidade intraguilda. Functional response compared between Harmonia axyridis (Pallas), Cycloneda sanguinea (Linnaeus) and Hippodamia convergens Guerin Meneville (Coleoptera: Coccinellidae) fed on Brevicoryne brassicae (Linnaeus) (Hemiptera: Aphididae) Abstract. The study evaluated the functional response of larval instars and adult of three species of coccinellids predator [Harmonia axyridis (Pallas), Cycloneda sanguinea (Linnaeus) and Hippodamia convergens Guerin Meneville] in different densities of Brevicoryne brassicae (Linnaeus), comparing the performance of the invasive species with the local species. It was observed that H. axyridis consumed more insects than the other species; the number of aphids preyed by the three species of coccinellids increased with the exchange of larval instars and that females tended to prey more aphids than males. The voracity of the 4th instar larvae is similar to that of adults, sometimes even larger, as in the case of C. sanguinea. Except for the first larval instar, all other stages of life have shown increased aphid consumption as the supply of prey increases. The results showed that the functional response of type III was indicated only by the 3rd instar larvae of H. axyridis and in the other species and stages evaluated the functional response was type II. In general H. axyridis presented asymptotes of the highest functional responses in comparison to the previously established species. However, the difference between the magnitude of the functional response curves between the invasive and the local species is not very pronounced, which may indicate little impact of the invasive on the population of resources in the field and a tendency to adaptation and stabilization between these species of the intraguild community.